Serum Leptin Levels in Women With Uterine Leiomyomas - Bihter Senem Dingiloglu; Tayfun Gungor; Bulent Ozdal; Sabri Cavkaytar; Umit Bilge; Leyla Mollamahmutoglu (Elsevier, 2007)
Objective: The purpose of this study was to examine the influence of leptin in women with uterine myoma. Materials and Methods: In this study, 38 women with myoma uteri and 30 normal women who applied to the Dr Zekai Tahir Burak Woman Health Research and Education Hospital's gynecology clinic were enrolled. Uterine leiomyomas were proved by pathology postoperatively. In all subjects, FSH, LH, E2, prolactin, hemoglobin, hematocrit, blood urea nitrogen, creatinine, fasting glucose, CA125, and leptin were examined, and body mass index (BMI) was calculated. Data were analyzed by Student's t test and Mann-Whitney U test. Results: Although leptin level was higher in the myomatic women (5.73 ± 4.08 ng/mL) than in the normal women, there was no statistically significant difference (p = 0.303). Also, no statistical difference in the ratios of leptin/BMI was found in both groups. A significant correlation was found between high E2 level and myoma uteri (p = 0.021). Hemoglobin levels were significantly lower in the myomatic women (p = 0.044). When we compared the leptin levels according to BMI, leptin levels were higher in patients who had BMI > 30 (p = 0.02). Conclusion: We did not find any significant difference in serum leptin levels between the two groups. But leptin may have an indirect role in the pathogenesis of uterine leiomyoma. So further research is needed to reveal the role of leptin in myoma uteri pathogenesis.